Türkiye sermaye piyasasında promosyon kampanyaları ve analizi - Uslu, Sevda (My University, 2017)
İngilizce “promotion” kelimesinin karşılığı olarak kullanılan tutundurma, satış çabaları, satış artırıcı çabalar, satış tahriki, satış teşviki, promosyon gibi kavramlarla da anılmaktadır.

The word ‘promotion’ is used specifically to refer publicity,sales effort and sales incentive.At the present time, It has become compulsory for businesses to persuade to sell goods or services, to create information channels, to differentiate from their competitors and to raise their awareness.
Keywords: Capital markets; Promosyon; Promosyon Kampanyaları; promotion; promotion campaigns; Psikolojik etkileri; Semaye piyasası; Sermaye Piyasası; Tutundurma; Türkiye